Literatuur en religie = Literature and Religion - Fraeters, Veerle; Nuyts, Tijl; Debergh, Gwennie (CAHIER VOOR LITERATUURWETENSCHAP, 2020)
In the aftermath of 9/11, religion made a comeback has made a comeback as a geopolitical and discursive reality. Literature too is increasingly turning its attention to religion in the cultural production of the past and present. This issue focuses on diverse literary traditions, confessions and methodological angles.